Galectin-3 in solid organ recipients: role in graft pathology and prospects for use - D. A. Velikiy; M. A. Osoblivaya; O. P. Shevchenko (Вестник трансплантологии и искусственных органов)
Galectin-3 (Gal-3) is an important regulator of cell adhesion, migration, proliferation, differentiation and apoptosis under pathophysiological conditions. It plays a crucial role in diseases associated with chronic inflammation and fibrosis. In recent years, there have been reports indicating changes in serum Gal-3 levels in solid organ transplant recipients in the verification of kidney, liver, heart and lung transplant pathologies. Studies on Gal-3 levels and dynamics in solid organ recipients may serve to assess graft conditions using new minimally invasive methods and to identify therapeutic targets for personalized therapy. The first clinical trial data on Gal-3 pharmacological inhibition are emerging. This review summarizes the current understanding of the role of Gal-3 in transplant pathology and the prospects for its use as a diagnostic marker and therapeutic target in solid organ recipients.